Muscle activation of the upper trapezius and functional typing performance during computer typing task: A comparison of two different wrist immobilization methods - YILDIZ ÖZER, AYSEL; SELÇUK, HALİT; KESKİN DİLBAY, NİLÜFER (ELSEVIER, 2021)
Background: The aim of this study was to examine the effect of two different wrist immobilization methods on the muscle activation of the upper trapezius muscle and functional typing performance during computer typing tasks in office workers. Methods: The study was conducted on 11 healthy office workers. The study subjects were asked to type on a computer for 5 min (1) without splint or taping, (2) with a splint, (3) with rigid taping which limits the wrist flexion at the dominant side. The upper trapezius muscle activation was recorded by surface EMG during the task. The mean values obtained from EMG were normalized according to Maximum Voluntary Isometric Contraction (MVIC), comparisons were made according to %MVIC. Results: The office workers' mean age was 27.45 +/- 3.64 years. There was no significant difference in immobilization methods between %MVIC on dominant (p = .508) and non-dominant (p = .213) sides. The upper trapezius of the non-dominant side showed higher electromyographic activity when the subjects used a splint (p = .013). There was a significant difference between splinting and rigid taping methods in typing performance (z =-2,491, p = .013). Conclusion: There is no significant difference in the upper trapezius muscle activation between the splint and rigid taping methods during the computer typing task on the dominant side. The typing performance was affected more during splint use compared to rigid tape application. Considering the importance of work efficiency in employees, rigid taping might be considered as an alternative splinting for wristimmobilization in office workers. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Surface electromyography; Upper trapezius; Orthosis; Taping; SHOULDER; WORK; ELECTROMYOGRAPHY; ORTHOSES; SUPPORT; BRACES